Exploring the Nature of Interactions in Science Classroom - Syahrir Idris (Muhammadiyah University of Mataram, 2019)
This article explores the nature of interactions in science classroom in order to enhance learning. Research in this area has attracted huge attention from many researchers evidenced in growing publications of this topic. Researchers have studied the topic from different angles and have covered different research avenues from structural patterns of interaction, joint construction of meaning, to the exercise of power relation, and to social identity construction. The researchers have examined how patterns of language use affect learning, how these patterns affect the equality, or inequality, of students’ learning opportunites, and how these patterns foster certain communicative competences. As the current focus may be too general for particular classroom, future research may need to focus on one aspect of the classroom interactions for more in depth analysis.